The Proline/Citrulline Ratio as a Biomarker for OAT Deficiency in Early Infancy - de Sain-van der Velden, Monique G. M. (Springer Berlin Heidelberg, 2012)
Deficiency of ornithine-δ-aminotransferase (OAT) in humans results in gyrate atrophy. Early diagnosis may allow initiation of treatment before irreversible damage has occurred. However, diagnosis is commonly delayed well into adulthood because of the nonspecific character of initial symptoms. Here, we report findings in a neonate who was evaluated because of a positive family history of OAT deficiency. The reversed enzymatic flux in early infancy resulted in borderline low ornithine concentration – evoking urea cycle disturbances – and increased proline. In addition, plasma citrulline was low. Consequently, the proline/citrulline ratio in plasma was increased compared to controls. To find out whether amino acid profiling in neonatal dried blood spots is suitable to detect OAT deficiency, we evaluated the original newborn dried blood spots of two affected patients and compared it with a database of >450,000 newborns tested in Minnesota since 2004. Proline concentrations (777 and 1,381 μmol/L) were above the 99 percentile (776 μmol/L) of the general population, and citrulline concentrations (4.5 and 4.9 μmol/L) only just above the 1 percentile (4.37 μmol/L). The proline/citrulline ratio was 172.9 and 281.8, respectively. This ratio was calculated retrospectively in the normal population, and the 99 percentile was 97.6. Applying this ratio for NBS could lead to early and specific detection of neonatal OAT deficiency, with no additional expense to newborn screening laboratories quantifying amino acids. Given that early diagnosis of OAT disease can lead to earlier treatment and prevent visual impairment, further studies are indicated to evaluate whether newborn screening for OAT deficiency is warranted.